Molecular Detection of Malaria Co-Infections with Some Arboviruses in Pregnant Women Attending Ante-Natal in Hospitals within Bauchi State, Nigeria - Joseph, Gloria Nyarim; Yakubu, Hauwa; Nannim, Nanvyat; Pam, Dung Davou; Dakul, Danaan Anthony (Sahel Journal of Life Sciences FUDMA, 2024)
Malaria and arboviruses are public health menaces, causing major morbidity in developing countries and are more severe in pregnancy leading to adverse effects which can lead to fetal and maternal death, hence, this study determined the prevalence of dengue, zika and malaria infections among pregnant women attending antenatal clinics in some hospitals within Bauchi Local Government Area, Bauchi State, Nigeria. One hundred and seventy-seven blood samples of pregnant women were collected and screened for malaria using the Rapid Diagnostic test kits, while the diagnosis for dengue and zika infections was done using real time Polymerase Chain Reaction (RT-qPCR). From the blood samples tested, 50 (28.25%) were positive for malaria, 1 (2.00%) sample was positive for dengue and dengue-malaria co-infection, however, no sample was positive for zika virus (0%). Malaria was recorded across all the age groups with a high statistical significance, dengue was prevalent between age 15-25years (2.35%) and 26-35years (1.35%) while dengue-malaria co-infection was only seen in age group 15-25years (1.18%). Pregnant women with fever and the trimesters were significantly associated with the prevalence of malaria (P<0.05 respectively); Educational qualification and occupation were significantly associated with dengue infections (P<0.05 for both) as well as dengue-malaria co-infection (P=0.05 for both), whereas history of miscarriages was only statistically associated with prevalence of dengue infections (P=0.02204). Despite the low prevalence of dengue virus among pregnant women in this study, the result of this study gives an overview of dengue, zika and malaria in Bauchi, thereby providing the first baseline data.